Process of pre-dilapidation on survey at Bandar Damai Perdana 56000 Cheras, Kuala Lumpur / Zarina Kadis - Kadis, Zarina (Universiti Teknologi Mara, Perak, 2016)
This report is about the pre-dilapidation survey work under the contractor MMC Pembentungan Langat Sdn.Bhd –PLSB. The site inspection at Bandar Damai Perdana Cheras,Kuala Lumpur. Practical training for four month one semesters, I have chosen to practical at Jasa Sendi (m) Sdn.Bhd Sri Gombak Batu Caves. For four Months beginning on the date of 1 June 2016 until 30 September 2016. Among the ongoing site visit at Bandar Damai Perdana Cheras Kuala Lumpur and completion of pre-dilapidation survey. Every week i visited the site for give the noticed 1 and 2 to the building surrounding the area 50m from the construction pipe line sewerage. I will inspect the building get permission from the owner in the building. I had the opportunity to learn how stages do pre-dilapidation survey. This training program indeed provide me a good chance to learn and Experience the real working environment. Through this exposure, I realize my ability and interest in this field. Hence, I know what field I should to participate in future. The practical training at JSSB is the best moment and all activities I have scheduled them in logbook weekly.